2003
DOI: 10.1038/sj.bjc.6600754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of quantitative real-time RT–PCR analysis of hTERT gene expression in human gliomas

Abstract: The presence of telomerase activity in a glioma may be a predictor of its malignant potential. Activation of telomerase is regulated at the transcriptional level of the human telomerase reverse transcriptase (hTERT). Here, we evaluated whether the amount of hTERT mRNA provides a molecular marker of glioma malignancy that would have clinical utility. We used a real-time RT -PCR to assess the number of hTERT transcripts in primary tumour samples derived from 70 glioma patients. Results were standardised by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 26 publications
4
33
0
3
Order By: Relevance
“…Similar results have been reported from other authors. Tchirkov et al (2003), using the same method, reported hTERT mRNA-positive expression in 69.8% of glioblastoma multiforme samples, when in the present study we found 66.6%. Kleinschmidt-DeMasters et al (2000) analysed by the TRAP method and found hTERT expression in 89% of glioblastoma samples.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results have been reported from other authors. Tchirkov et al (2003), using the same method, reported hTERT mRNA-positive expression in 69.8% of glioblastoma multiforme samples, when in the present study we found 66.6%. Kleinschmidt-DeMasters et al (2000) analysed by the TRAP method and found hTERT expression in 89% of glioblastoma samples.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, four out of 18 meningiomas and three out of eight grade I meningiomas were positive for hTERT mRNA expression (data not shown), suggesting also a trend for increased expression with histologic grading of meningiomas. On the other hand, studies by Falchetti et al (1999), Harada et al (2000), Cabuy and de Ridder (2001) and Tchirkov et al (2003) have generated conflicting results regarding the prognostic utility of telomerase expression in meningiomas and gliomas (predominantly of high grade).…”
Section: Discussionmentioning
confidence: 99%
“…Activations of the hTERT or ALT pathways are obligate for senescence bypass and for neoplastic transformation of normal cells (Newbold, 2002). Telomerase activity and/or hTERT expression are increased in cancers and are prognostic factors in various cancer types (Harada et al, 1999;Bieche et al, 2000;Lee et al, 2001;Marchetti et al, 2002;Wang et al, 2002;Fujita et al, 2003;Krams et al, 2003;Ohali et al, 2003;Tchirkov et al, 2003;Lantuejoul et al, 2004). However, the clinical impact of hTERT expression or activity in non-small-cell lung cancer (NSCLC) remains controversial (Albanell et al, 1997;Taga et al, 1999;Hirashima et al, 2000;Komiya et al, 2000;Toomey et al, 2001;Marchetti et al, 2002;Wang et al, 2002;Fujita et al, 2003;Wu et al, 2003;Hsu et al, 2004;Lantuejoul et al, 2004).…”
mentioning
confidence: 99%
“…This makes hTERT as an excellent candidate gene to target in anticancer therapy (Shay et al 2001;Cong et al 2002). It has been reported that, more than 50 % of gliomas have increased telomerase activity (Langford et al 1995;Nakatani et al 1997;Le et al 1998;Sugita et al 2000;Tchirkov et al 2003). Several studies showed that, silencing of hTERT resulted in progressive shortening of telomeres and thereby inhibiting cellular proliferation and induce apoptosis in various cancer cells (Natarajan et al 2004;Zhao et al 2005;Wang et al 2007;Shi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 80-90 % of human cancers display telomerase activity. Several studies showed that more than 50 % of gliomas display telomerase activity and its detection rates increases with the grades of malignancy (Langford et al 1995;Nakatani et al 1997;Sano et al 1998;Tchirkov et al 2003). Much attention has been given to telomerase, however, telomerase independent mechanism like alternative lengthening of telomeres (ALT) can also maintain telomere lengths in cancer cells by homologous recombination between telomere sister chromatids (Cesare and Reddel 2010).…”
Section: Introductionmentioning
confidence: 99%